576 NL-201, a de novo IL-2 and IL-15 agonist, demonstrates enhanced in vivo antitumor activity in combination with multiple cancer immunotherapies. (9th November 2020) - Walkey, Carl; Swanson, Ryan; Ulge, Umut; Silva Manzano, Daniel Adriano; Drachman, Jonathan
Abstract : Background: NL-201 is a de novo IL-2 and IL-15 receptor agonist designed with enhanced affinity for IL-2Rβγ and no binding interface for IL-2Rα (CD25). Previously, we reported that NL-201 stimulates selective proliferation of CD8+ effector T cells and NK cells, leading to increased CD8:Treg and NK:Treg ratios in the tumor microenvironment. As a result, NL-201 treatment led to robust single-agent antitumor activity in syngeneic murine tumor models at well-tolerated doses. Methods: Here, we evaluated the antitumor activity of NL-201 in combination with established and exploratory cancer immunotherapies, including tumor-targeting monoclonal antibodies and immune checkpoint inhibitors (CPIs). Specifically, we evaluated NL-201 in combination with an anti-gp75 antibody (TA99) in a murine melanoma model, or anti-PD-1 and anti-PD-L1 antibodies in a CPI-resistant murine colon cancer model. Results: NL-201 synergizes with TA99, anti-PD-1, and anti-PD-L1 to inhibit tumor growth more effectively than either agent alone. The synergy of NL-201 with TA99 may result from enhanced NK-mediated antibody-dependent cellular cytotoxicity (ADCC), while the synergy with CPIs may result from CD8+ T cell stimulation, which can turn 'cold' tumor microenvironments 'hot'. Conclusions: The broad activity of NL-201 across diverse tumor models and its potential to be combined with a variety of established and exploratory cancer immunotherapies to achieve synergistic antitumor activity highlights the opportunity for NL-201 to become a critical component of future immunotherapy regimens.